Targeting JNKs with systemic viruses towards a mechanistic understanding of anxiety-like behaviour - Jokela, Anniina (My University, 2022)
Depression and anxiety disorders are one of the most common mental health conditions. To develop better treatments for the disorders, it is necessary to understand their mechanisms better. Genetic aberrations on the c-Jun amino-terminal kinase (JNK) pathway are associated with neuropsychiatric disorders such as schizophrenia and autism. However, their mechanism of action in the context of these diseases is unknown. The Coffey lab identified that inhibition of JNK solely in the mouse brain leads to low anxiety- and low depressive-like phenotypes. This study aimed to examine the effect of JNK inhibition in the brain to better understand how JNK contributes to depressive- and anxiety-related behaviours and cognition in mice by exploiting the recently developed systemically administered adeno-associated viruses (AAV). Mice were injected with either an mRuby2 tagged nuclear-targeted JNK-inhibitor expressed in the AAV-PHP.eB vector with a ubiquitous promoter or a control vector expressing mRuby2 alone. The behaviour of the mice was assessed with the open field, elevated plus maze, novel object recognition, Y-maze, and forced swim tests. After behavioural testing, the viruses were visualized in the perfused mouse brains by immunostaining. Our results identified that non-cell-specific inhibition of JNK using systemic AAVs led to significantly reduced motility in mice. However, it did not elicit a prominent effect on anxiety-like behaviour, and there was no treatment effect on depressive-related behaviour or cognition. In conclusion, this project gives useful information on baseline effects of systemic AAVs on commonly used mouse behaviour tests and specific information on JNK function in controlling anxiety-like responses.
Keywords: Anxiety Disorders, Depression, c-Jun Amino-Terminal Kinase, Adeno-Associated Virus